Evaluación de la actividad proteolítica del manto del calamar gigante (Dosidicus gigas) - Dublán García, Octavio (Universidad Autónoma Metropolitana, 2001)
Giant squid is one of the main species captured off the pacific coast of Mexico. Although it is an excellent source of protein, it is not widely consumed due to their characteristic flavor and low functionality. The last as a result of an intense endogenous proteolytic activity, that is more evident after death and leads to a rapid muscle autolysis during storage with the consequently lost in texture and functionality. However, few reports were found in the literature regarding to specific enzymes present in this mollusk. Therefore the main objective was to characterize the endogenous proteases of giant squid mantle muscle according to their molecular weight profile, pH, temperature and inhibitors response. Also, to evaluate changes associated to proteolysis during chill storage. This work was developed in the Area of Bioquímica de Macromoléculas, Biotecnología, UAM-Iztapalapa. First, The proteolytic activity of the mantle muscle of giant squid (Dosidicus gigas) was characterized for its pH and temperature optima, and response to proteinase inhibitors. Extracts were prepared by homogenization of mantle with phosphate buffer (pH 7, 20 mM), activity was assayed using hemoglobin and casein as substrates. Then, proteases were isolated by sequential ammonium sulfate precipitation, followed by gel filtration or cationic exchange chromatography and SDS-PAGE. High proteolytic activity was detected at 35 "C in both acidic and alkaline pH ranges with optimal activity at the following pH values 2.7, 3.1 6.1 and 7.6. Proteases were strongly inhibited by leupeptin, pepstatin, chymostatin, and trypsin inhibitor although pyrophosphate, EDTA, iodoacetamide, CaC12 and PMSF had lower inhibitor response. The molecular weights obtained by SDS-PAGE ranged from 11,000 to 395,000 Da. Therefore, it was concluded that several enzymes such as acid-, thiol- and serin-proteases may be related to the endogenous squid proteolytic activity. On a second stage, changes associated to proteolysis of mantle muscle during chill storage were studied. Portions of mantle were vacuum packed and stored at 4°C during eight days. Water holding capacity (WHC), color, pH, shear stress and scanning electronic microscopy analysis were carried out. WHC and pH increased during storage, but after day 4 these values remained constant. Dissociation of the protein-pigment complex by proteases brought about changes in color. Finally, electron micrographs showed considerable connective tissue degradation and fiber deformation; also, shear stress values decreased throughout the storage. Structural degradation of mantle muscle and high pH values were responsible of the increase in WHC, but lost of textural properties were mainly due to the endogenous protease activity. Results showed that giant squid mantle is damaged by endogenous proteases and they must be considered in order to prevent protein degradation to increase shelf-life and extend the processing alternatives of this resource. Some protease inhibitors used in this theses are no allowed by the food legislation therefore, it is advised for future studies to look for alternative methods of enzyme inactivation, as pH and temperature control, as well the use of high pressure. In the Same way, it is necessary to make future studies regarding collagen degradation, as it related to mantle softness during storage. Finally, it is recommended to carry out histological studies in order to identify the specific structures that are degraded during storage.; El calamar gigante (Dosidicus gigas) es un cefalópodo encontrado en abundancia en los litorales de México. El consumo de este molusco en forma fresca es muy bajo, debido a que la población mexicana no esta acostumbrada a consumir este producto por ser poco conocido comercialmente, además por presentar un aspecto poco agradable. Aproximadamente el 80 % del volumen de captura es exportado a España y Corea, en donde su consumo es muy elevado. Sin embargo cuando el calamar llega a su destino, presenta cierto estado de degradación probablemente ocasionado por la intensa actividad proteolítica en el manto. Este trabajo se llevó a cabo en el laboratorio de Bioquímica de Macromoléculas del Departamento de Biotecnología de la UAM-Iztapalapa, y se realizó en dos partes. Primero se caracterizaron parcialmente las proteasas presentes en esta especie. Se determinó el pH y la temperatura de actividad óptima utilizando como sustratos hemoglobina y caseína, y se calculó el perfil de pesos moleculares de las proteínas presentes en el extracto enzimático. La actividad proteolítica en el extracto del manto del calamar gigante, fue máxima a 35 "C, se detectaron varios picos de actividad en el intervalo de pH estudiado ( 2.7, 3.1, 6.1, 7.3 y 7.6). El peso molecular de proteínas y péptidos encontrados en el extracto fue en un intervalo de 11,000 a 395,000 Da. Se determinó el tipo de enzimas que podrían estar presentes en el músculo del calamar, mediante la adición de varios inhibidores de proteasas. Se observó que la actividad proteolítica fue inhibida por leupetina A, quimostatina, pepstatina e inhibidor de tripsina, principalmente, y en menor medida por pirofosfato, EDTA, iodoacetamida, CaC12 y PMSF, lo cual podría dar un indicio de la presencia de diversas enzimas tales como serin, cistein, aspártico y metalo proteasas que son algunas de las proteasas implicadas en el deterioro de la textura y color de los productos marinos. En la segunda parte de este trabajo se observó la acción de proteasas sobre el músculo durante el almacenamiento en refrigeración. Evaluando algunos parámetros de calidad asociados a la integridad de proteínas musculares como textura, color, capacidad de retención de agua y pH, así como cambios de la estructura del músculo del calamar mediante la observación por microscopía electrónica de barrido, todo esto durante un periodo de almacenamiento en refrigeración. La fuerza al corte diminuyó significativamente durante los 8 días de almacenamiento, debido a la autólisis sufrida por la acción de las proteasas endógenas presentes en el músculo. El pH y la CRA se incrementaron durante el tiempo de estudio, debido principalmente a la aparición de grupos amino provenientes de la formación de dimetilamina y posible degradación de proteínas. El color varió durante el almacenamiento, esto podría ser debido a la autólisis de los complejos pigmento-proteína responsables del color del tejido muscular. Finalmente, la microscopía electrónica de barrido, mostró la degradación de colágeno, aparición de espacios entre las células musculares y deformación de fibras musculares. En este trabajo se demostró que la calidad del manto del calamar gigante es alterada por las enzimas proteolíticas presentes en éste, y debido a que algunos de los inhibidores utilizados no se permiten por la legislación alimentaría, se recomienda para trabajos posteriores, utilizar métodos alternos para llevar a cabo la inactivación de las enzimas, como control del pH y temperatura, así como la utilización de altas presiones, procurando no afectar tanto sus características organolépticas como las de calidad. Asimismo es necesario llevar acabo estudios más específicos sobre actividad de las colagenasas, ya que son una de las responsables en la degradación del colágeno dando como resultado el ablandamiento del músculo del calamar durante el almacenamiento.